Expansion Clauses Application in Pan Balang Tamak Text (e-Journal of Linguistics, 2020)
Pan Balang Tamak text is one of famous Balinese texts in Balinesecommunity. However, the popularity of the text has declined sincemore than years ago especially in the youth. This is because of moreinteresting and modern entertainment. This phenomenon made thestakeholders feel worried because it led it to get extinct therefore, thestake holders anticipated it. One of the efforts to prevent from theextinct was to write Pan Balang Tamak text. The text was written insome version with their own styles. However, the essence of allvariances is similar. The text belongs to be narrative text therefore itneeds more abstract comprehension to find the character of the figures,message and ideology of the text. Most of the communitiescomprehended the text from literal point of view. This was the reasonwhy the text was viewed to have different interpretation about thecharacters of the text. Besides that, the clauses within the complexeswere not comprehended well based on the functions in the clausescomplexes. To find the characteristic of the figures of the text,expansion clause becomes prime concern. This paper analyzed theclause functions within the expansion clauses. The data were takenfrom Satua satua Bali Pan Balang Tamak (2014). The theory used toanalyze the data was the theory of clause complex proposed byHalliday. The method hired for this research was library research bysyntactical technique. The finding of the research suggested that allkinds of expansion clause be hired in the text such as: elaboration,extension and enhancement. Enhancement clauses were found in themost varieties. Elaboration and expansion in paratactic clausesindicated that Pan Balang Tamak did something different from othersdid while enhancement clauses in hypotactic indicated that Pan BalangTamak became target.
Keywords: Expansion clauses; Pan Balang Tamak jero klian; paratactic; hypotactic